A multi-item inventory model for small business - a perspective from India. (2nd April 2019) - Shenoy, Dinesh; Mal, Hoshiar
Micro, small and medium enterprises (MSMEs) in India are focused on improving their inventory management function as part of government's program to increase their contribution to the gross domestic product (GDP). A plethora of inventory models are available in literature; these models are either very complex, or need reliable inventory cost data, or are not applicable to all classes of items and are, therefore, rendered ineffective. In this paper we have developed and presented a simple, yet effective, model that combines the characteristics of selective inventory control (SIC) and an exchange curve (EC). Combination of these techniques not only allows determination of ordering policy for all items, but also involves managers in decision making, thus providing MSMEs with a solution that is robust and practical. We also describe application of this model to a sample of 30 items in an auto components manufacturing firm. The case study demonstrates ease of implementation of the proposed model as well as solution completeness.